Efficient back-off mechanism for IEEE 802.15.4 wireless sensor networks - Qadawi, Zahraa D.A. (2013)
In recent years, the demand for Wireless Sensor Networks (WSNs) has increased tremendously and gained world-wide interest. Their importance has been enforced by the fast delivery of several medium access control protocols. MAC protocols provide a great influence over the communication mechanisms and play a significant role in the performance of sensor networks. One of the major protocols of our interest is MAC protocol. Different contention-based MAC Protocols for Wireless Sensor Networks (WSNs) have been proposed over the last few years. IEEE 802.15.4 is one of the most prominent MAC protocol standard designed for low-power, low-cost, and low-rate Wireless Personal Area Networks (LR-WPANs). The Contention Access Period (CAP) of IEEE 802.15.4 utilizes Carrier Sense Multiple Access with Collision. Avoidance (CSMA-CA) algorithm for its contention and channel access. In CSMACA,a long random backoff time causes longer average delay and lower channel utilization, while a small one gives high collision rate. Therefore, this thesis examines two main drawbacks of CSMA-CA algorithm; the first problem is that during CSMACA mechanism, a node tends to delay for a very limited number of backoff exponent (BE). The probability of collisions when two or more nodes choose the same number of backoff period is high. This insufficient backoff time affects system performance by causing more collisions among the contending nodes. The second problem is that CSMA-CA updates the contention window length without considering the number of contending nodes in the communication medium. Therefore, CSMA-CA is inefficient in terms of system throughput, reliability and energy efficiency. Thus, it is evident CSMA-CA degrades network performance as we will be demonstrated later and this otivates us to introduce a better backoff algorithm. In this thesis, we propose EBA-15.4MAC that enhances the IEEE 802.15.4 MAC protocol. EBA-15.4MAC is based on two new important techniques; firstly, it updates he contention window size based on the probability of collision parameter. In other words, when the number of nodes increases in the network, the probability of collision will increase as well, so we include the probability of collision as a parameter to adapt the CW size. Hence, when the number of nodes increases in the network, a node delay for an extended period of time to give the nodes better opportunities to access the medium and therefore reduces contention among the nodes. On the other hand, when the level of collision decreases due to lesser number of nodes, nodes tend to delay for a shorter durations. Secondly, to increase the efficiency of EBA-15.4MAC algorithm, we propose a new scheme to resolve the problem of access collision arising from the small number of backoff exponent used by CSMA-CA. In this scheme, we allow the nodes to delay for a random backoff periods by employing a novel Temporary Backoff (TB) and Next Temporary Backoff (NTB). In this case, the nodes not only choose BE randomly as mentioned in the standard but they select TB and NTB between 10% to 50% of the actual backoff delay selected randomly by the node. By including a random selection of TB and NTB value within the whole existing backoff delay, EBA-15.4MAC minimizes the level of collision since the probability of two nodes selecting the same backoff period will be very low. By using these two new methods, the proposed algorithm significantly improves the overall system performance of IEEE 802.15.4. To evaluate the performance of EBA-15.4MAC mechanism, the network simulator (NS-2) has been conducted. Simulation results indicate that EBA-15.4MAC outperforms significantly the IEEE 802.15.4 MAC protocol. Furthermore, it also significantly improve system throughput by up to 32% compared to the existing standard. It is also shown that, with a more appropriate MAC parameters setting, it is possible to reduce collision probability and achieve 99% delivery ratio. Furthermore,minimized energy consumption is achieved by approximately 15% especially for higher traffic load. In addition, it is shown that EBA-15.4MAC is able to maintain a very low average packet delay till 1.5packets/second traffic load compared to that of only 1.2packets/second for 802.15.4. Finally, it can be concluded that EBA-15.4MAC outperforms the original IEEE 802.15.4 MAC protocol.